Relationship Between History Of Hypertension And The Incidence Of Preeclampsia-Eclampsia In Pregnant Women - Nur Azizah Reski Amir; Masita Fujiko; Kartika Handayani (Sean Institute, 2024)
Hypertension is one of the significant health problems worldwide, including in Indonesia. Preeclampsia is a medical condition characterized by increased blood pressure and the presence of protein in the urine after 20 weeks of gestation. If left untreated, preeclampsia can develop into eclampsia. Preeclampsia and eclampsia are two conditions that can endanger the lives of the mother and fetus, and require immediate medical attention. This study aims to determine the relationship between a history of previous hypertension and the incidence of preeclampsia-eclampsia in pregnant women. The method used is literature review with Narrative design Review to identify and summarize previously published articles on the relationship between history of hypertension and the incidence of preeclampsia-eclampsia in pregnant women. From 10 articles summarized, the results of the study showed that pregnant women with a history of hypertension had a significantly higher risk of experiencing preeclampsia-eclampsia compared to those without such a history. This finding emphasizes the importance of intensive medical supervision during pregnancy to monitor and manage the health conditions of pregnant women appropriately.